Self Harm in Polytechnic Students of the Ministry of Health of East Kalimantan in 2025 - Gajali Rahman; Tini; Lukman Nulhakim (Afiyatun Journal of Health Sciences, 2025)
Background: Self-harm behavior is a serious concern among college students who face high academic pressure, dense study loads, and strict time demands. This study aimed to identify and describe factors contributing to self-harm behavior among Nursing and Midwifery students at Poltekkes Kemenkes Kaltim in 2025. Methods: This descriptive study used a qualitative approach with deep interview technique. The sample consisted of 104 respondents selected through purposive sampling. Data collection used questionnaires and observations. Data validity was ensured through observation persistence and triangulation techniques. Results: The study found that 59 respondents (56.7%) had a tendency toward self-harm behavior. The majority were female (47.7%), aged 15-20 years (50.85%), in semester 4 (44%), and with parental income of Rp.1,000,000-Rp.5,000,000 (60.2%). Common behaviors included self-blame, neglecting wounds, reckless driving, and self-hitting. Conclusion: Self-harm behavior among students requires immediate attention. This research contributes to understanding self-harm behavior so that perpetrators can seek psychological treatment before it develops into actual suicide attempts.